Explicit inverse of the Pascal matrix plus one - Sheng-liang Yang; Zhong-kui Liu (International Journal of Mathematics and Mathematical Sciences)
This paper presents a simple approach to invert the matrix Pn+In by applying the Euler polynomials and Bernoulli numbers, where Pn is the Pascal matrix.